Why do personal and demographic data matter in healthcare digitalization initiatives? - Stanimirovic, Dalibor; Jocic, Lucija Tepej; Stanimirovic, Tatjana (Edelweiss Applied Science and Technology, 2026)
This study explores the role and usability of personal and demographic data (PDD) in Slovenian healthcare digitalization initiatives, assessing its impact on clinical aspects, operative procedures, public health policymaking, and cross-border health threats. Using a multiple-case study approach, data were collected from expert focus groups and supported by intelligence reports from the Central Register of Patient Data. Data were coded using a content analysis approach and utilized to enhance the understanding of the research subject and refine our inferences. PDD, including identifiers, residence details, education level, employment status, social history, lifestyle behaviors, cultural determinants, and other related information, is vital for effective healthcare delivery, public health surveillance, administrative and financial compliance of the healthcare system’s operations, and cross-border actions. The study highlights the pivotal role of PDD in the Slovenian eHealth system through real-world cases and applications. The key findings suggest that leveraging the potential of PDD requires systemic improvements, particularly in national strategy and regulation, data collection and quality, data utilization and integration, and privacy and ethical considerations. Advancing these areas through a coordinated and comprehensive approach can maximize the value of PDD and serve as a model for other countries aiming to strengthen their digital health systems.